2002
DOI: 10.1038/sj.bjc.6600595
|View full text |Cite
|
Sign up to set email alerts
|

Association of p53 codon 72 polymorphism with advanced lung cancer: the Arg allele is preferentially retained in tumours arising in Arg/Pro germline heterozygotes

Abstract: The association of p53 codon 72 polymorphism with cancer has been investigated by several scientific groups with controversial results. In the present study, we examined the genotypic frequency of this polymorphism in 54 patients with advanced lung cancer and 99 normal controls from the geographical region of Greece. Sputum and bronchial washing samples from each patient were assayed for the presence of human papillomavirus. Codon 72 heterozygous (Arg/Pro) patients were also analysed for loss of heterozygosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
2
9

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 37 publications
6
53
2
9
Order By: Relevance
“…Several reports indicated that the 72R allele is preferentially mutated and retained in various human tumors (Kawaguchi et al, 2000;Marin et al, 2000;Tada et al, 2001;Langerod et al, 2002;Papadakis et al, 2002;Anzola et al, 2003;Schneider-Stock et al, 2004a;Hsieh et al, 2005), and is associated with the presence of p53 overexpression (Lee et al, 2006). In experiments, mutant 72R allele tended to block p73 function more effectively than mutant 72P isoform, which might lead to a higher tendency of p53 mutation in tumors .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several reports indicated that the 72R allele is preferentially mutated and retained in various human tumors (Kawaguchi et al, 2000;Marin et al, 2000;Tada et al, 2001;Langerod et al, 2002;Papadakis et al, 2002;Anzola et al, 2003;Schneider-Stock et al, 2004a;Hsieh et al, 2005), and is associated with the presence of p53 overexpression (Lee et al, 2006). In experiments, mutant 72R allele tended to block p73 function more effectively than mutant 72P isoform, which might lead to a higher tendency of p53 mutation in tumors .…”
Section: Discussionmentioning
confidence: 84%
“…The 72R allele of mutant p53 has been found to have greater ability to bind p73, neutralizing p73-induced apoptosis, when compared to the mutant 72P allele . Moreover, the 72R allele is preferentially mutated and retained in various human tumors arising in RP germline heterozygotes Kawaguchi et al, 2000;Tada et al, 2001;Langerod et al, 2002;Papadakis et al, 2002;Anzola et al, 2003;Schneider-Stock et al, 2004a;Hsieh et al, 2005). Recently a positive association of the 72R allele with p53 overexpression has been reported in esophageal cancer tissue (Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has also been seen in colorectal cancer [15], squamous cell carcinomas [20], ovarian carcinomas 123 [21], and lung cancer [22], as well as in cancers involving esophagus, and the urinary tract [23,24]. The biological significance of these univocal findings seems unclear.…”
Section: Discussionmentioning
confidence: 97%
“…O polimorfismo ocorre por simples substituição de uma base no códon que resulta em alteração estrutural da proteína p53 (24) . Vários autores têm demonstrado que a presença de Arg/Arg confere maior risco de desenvolvimento de tumores, como em cânceres de bexiga, cérvix uterino (22) , mama (16) , pulmão (17) , etc. Entretanto, no câncer colorretal não há uma associação clara com este polimorfismo e aumento do risco de câncer (10) .…”
Section: Estudo Do Polimorfismo Genético No Gene P53 (Códon 72) Em Câunclassified